Furunkulózní myiaza- 2 kazuistiky - Hozáková, Lubomíra; Rožnovský, Luděk; Doležil, Zdeněk; Doležílková, Jana (Klinicka mikrobiologie a infekcni lekarstvi, 2015)
Furuncular myiasis caused by the larvae of the human botfly, Dermatobia hominis, is a common disease in tropical areas of Latin America and may therefore occur in travelers returning from that region. Outside the endemic areas, the diagnosis is often delayed because the disease is mistaken for a bacterial skin infection. Reported are two cases of furuncular myiasis in patients returning from Central and South America.
Keywords: Larva; Animals; Humans; myiáza; lidé; Myiasis; Diptera; zvířata; larva